Pengaruh Efektivitas Robot AI Berbasis Images Preprocessing Terhadap Kepuasan Pengguna Dalam Mendeteksi Kematangan Buah Tomat - salsi kirana sya'bani; Nur Aziezah; Hikmah Rahmah; Ridwan Siskandar; Aep Setiawan (International Forum of Researchers and Lecturers, 2024)
This research aims to demonstrate the influence of the effectiveness of image preprocessing-based artificial intelligence technology in detecting the ripeness level of tomatoes on user satisfaction and to discover correlations between them. The applied research method is quantitative, with data collected through the distribution of questionnaires to attendees of the IT Festival 2023 Expo held on Sunday, August 27, 2023, at the Baranangsiang Campus, IPB. The data analysis methods used include Pearson correlation test, simple linear regression, coefficient of determination test, and T-test using SPSS 25.0 software. The test results indicate that the effectiveness of image preprocessing-based artificial intelligence technology has a positive and significant impact on detecting the ripeness level of tomatoes